The development of stocked eels (Anguilla anguilla) in previously eel‐free Austrian Alpine lakes. Issue 1 (10th September 2014) - Essl, Katharina; Gassner, Hubert; Schabetsberger, Robert; Jagsch, Albert; Kaiser, Roland
Abstract: Over a period of 34 years (1954–1987), a total of 11.9 million glass eels were stocked all over Austria to improve the yields of commercial fishermen and to make the lakes more attractive for anglers. Nearly half (48%) of the imported glass eels were introduced into natural, previously eel‐free Alpine lakes until stocking ceased in 1988. Twenty‐five years later, their occurrence could be verified in 56% ( N = 22) of the Austrian Alpine lakes larger than 50 ha and mean body length had increased to 66 cm. Eels from seven selected Austrian Alpine lakes exhibited a yearly mean increase in length between 0.6 and 1.5 cm, indicating a comparatively poor growth compared with the majority of eel populations from within their natural distribution range. At the same time, high expectations in developing a flourishing eel fishery were not met. In all but one lake, the harvest remained below 3% of the total yearly catch and salmonids remained the dominant target species. During peak harvest in the 1980s, it exceeded 8% in mesotrophic Wallersee (2600 kg). Simulations of stock development indicated that the yield could have been improved, but contrary to earlier expectations eels never became important for local cuisine and catches remained too low for the development of a profitable export business. On the other hand, eels may have contributed to the loss of small‐bodied fish taxa.